Mehanske in trdnostne analize v podporo zamenjavi uparjalnikov in povečanju moči JE Krško - Krajnc, Božidar (Strojniški vestnik, 2000)
Krško nuclear power plant (NPP) is one the last presurized water reactor NPPs of western design in Europe, which has decided to replace the existing steam generators and at the same time perform a power uprating. A compehensive set of design calculations and safety analyses have been performed to demonstrate: -that the new steam generators are compatible with the existing plant, - that the plant can operate safely and with adequate margins at the uprated power. In this power only the mechanical and structural analyses are presented. This analyses meet, as veryfied by independent evaluations, high quality standards and ensure the safe operation of Krško NPP after the replacement of the steam generators and the power uprating.
Keywords: celovitost; analize mehanske; analize trdnostne; puščanje pred zlomom (LBB); Nuklearna elektrarna Krško; reaktorska tehnika; hladilni sistemi; trdnost; analize; preizkušanje